Identification and enzymatic characterization of acid phosphatase from Burkholderia gladioli - Rombola, Tiago Henrique [UNESP]; Pedrinho, Eliamar Aparecida Nascimbem [UNESP]; Lemos, Eliana Gertrudes Macedo [UNESP]; Gonçalves, Adriano Marques [UNESP]; Santos, Luiz Flávio José dos [UNESP]; Pizauro Júnior, João Martins [UNESP] (Springer Nature, 2014)
Background: The genus Burkholderia is widespread in diverse ecological niches, the majority of known species are soil bacteria that exhibit different types of non-pathogenic interactions with plants. Burkholderia species are versatile organisms that solubilize insoluble minerals through the production of organic acids, which increase the availability of nutrients for the plant. Therefore these bacteria are promising candidates for biotechnological applications. Results: Burkholderia sp. (R 3.25 isolate) was isolated from agricultural soil in Ponta Grossa-PR-Brazil and identified through analysis of the 16S rDNA as a strain classified as Burkholderia gladioli. The expression of membrane-bound acid phosphatase (MBAcP) was strictly regulated with optimal expression at a concentration of phosphorus 5 mM. The apparent optimum pH for the hydrolysis of p-nitrophenylphosphate (PNPP) was 6.0. The hydrolysis of PNPP by the enzyme exhibited a hyperbolic relationship with increasing concentration of substrate and no inhibition by excess of substrate was observed. Kinetic data revealed that the hydrolysis of PNPP exhibited cooperative kinetics with n = 1.3, Vm = 113.5 U/mg and K0.5 = 65 μM. The PNPPase activity was inhibited by vanadate, p-hydroxymercuribenzoate, arsenate and phosphate, however the activity was not inhibited by calcium, levamisole, sodium tartrate, EDTA, zinc, magnesium, cobalt, ouabain, oligomycin or pantoprazol. Conclusion: The synthesis of membrane-bound non-specific acid phosphatase, strictly regulated by phosphate, and its properties suggest that this bacterium has a potential biotechnological application to solubilize phosphate in soils with low levels of this element, for specific crops.
Keywords: Phosphohydrolase; Inhibition; Phosphate; P-Nitrophenylphosphate; Solubilization